85 nm wide-band tunable erbium doped fiber laser using a gallium selenide (GaSe)-based saturable absorber for passive optical modulation - Ahmad, Harith; Aidit, Siti Nabila; Thambiratnam, Kavintheran (IOP Publishing, 2019)
A wide-band and tunable passively optically modulated fiber laser using a gallium selenide (GaSe) based saturable absorber (SA) is proposed and demonstrated. The GaSe-based SA is prepared by mechanical exfoliation and is able to generate self-starting pulses that have a maximum repetition rate of 57.9 kHz and minimum pulse width of 3.6 s. The highest pulse energy generated by the pulse laser is 30 nJ. The laser has wide-band tunability covering a broad wavelength range of 1501 nm to 1586 nm, giving a total tuning range of over 85 nm. The proposed laser would have potential for use in various optical telecommunications and measurement applications. © 2019 Astro Ltd.